2022
DOI: 10.3390/ijms23137360
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Equine Endometrosis: The NF-κB-Dependent Pathway Underlies the Ovarian Steroid Receptors’ Dysfunction

Abstract: Endometrosis is a frequently occurring disease decreasing mares’ fertility. Thus, it is an important disease of the endometrium associated with epithelial and stromal cell alterations, endometrium gland degeneration and periglandular fibrosis. Multiple degenerative changes are found in uterine mucosa, the endometrium. However, their pathogenesis is not well known. It is thought that nuclear factor-κB (NF-κB), a cell metabolism regulator, and its activation pathways take part in it. The transcription of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…It has been demonstrated that estrogens exert their actions by binding to the estrogen receptor. Except the classic nuclear receptors ERα and ERβ, which have been detected in uteri and the expression of ERα and ERβ in the endometrium is changed in relation to the phase of the ovarian cycle and endometrial disease (Jasiński et al, 2022; Schams & Berisha, 2002), the estrogen membrane receptor GPER was also detected in the uteri (Kolkova et al, 2010). Our results showed that GPER was expressed in the bovine endometrium, and its expression level was significantly higher in the healthy endometria than that in the endometria with endometritis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that estrogens exert their actions by binding to the estrogen receptor. Except the classic nuclear receptors ERα and ERβ, which have been detected in uteri and the expression of ERα and ERβ in the endometrium is changed in relation to the phase of the ovarian cycle and endometrial disease (Jasiński et al, 2022; Schams & Berisha, 2002), the estrogen membrane receptor GPER was also detected in the uteri (Kolkova et al, 2010). Our results showed that GPER was expressed in the bovine endometrium, and its expression level was significantly higher in the healthy endometria than that in the endometria with endometritis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a study provided evidence that thyroid hormones dysregulation alters NOSs profiles, which suggested that NOSs/NO is possibly involved in the regulation of female reproduction [71]. Recent studies have reported the relation of nuclear factor kappaB (NF-κB) with endometrosis, a serious problem that mainly affects the fertility of older mares [72][73][74]. And one of the genes associated with a region with TRD is the RELA gene that belongs to the subunits NF-κB.…”
Section: Plos Onementioning
confidence: 99%